Determining solar irradiance on inclined planes from classified CIE (International Commission on Illumination) standard skies. (15th April 2016) - Li, Danny H.W.; Lou, Siwei; Lam, Joseph C.; Wu, Ronald H.T.
Abstract: Solar irradiance data particularly on inclined planes are crucial to solar energy applications and energy-efficient building designs. However, the basic solar data for the planes of interest are not always readily available. Recently, the CIE (International Commission on Illumination) adopted a range of 15 standard skies which provide a good overall framework for representing the actual sky conditions. Each sky represents a unique sky-diffuse distribution. Upon the classification of the standard skies, the solar irradiance data at the plane of interest can be computed. This paper presents a method to estimate the solar irradiance on inclined plane based on the CIE Standard Skies. Data recorded in Hong Kong from the end of February to early June in 2015 were used to validate the calculation procedures. The results show that the approach can accurately estimate solar irradiance on inclined planes. Highlights: The inclined sky components at various scattering angles are presented. The steps for estimating the solar irradiance on titled planes are established. The performance of the proposed approach is evaluated and reported.